Controversy and humor: possible interfaces in Juma Aiuba’s chronicle - Wilson, Francelino (2020)
In the chronicle The “Past-perfect” of life, (O “pretérito mais-que-perfeito” da vida), Juma Aiuba inscribes his speech in two isotopies, i.e. the case of hidden debts and the pandemic of the new coronavirus. This writing model proves to be challenging to discourse analysis, even because it arouses interest in understanding the author’s standard and the enunciator’s marks. In the integrated perspective of Jean-Michel Adam (2001), to the light of the multiple categories, we analyze for the purpose of helping define the standard of JA’s writing and discuss polemics and humor as “connivent” discursive categories in opinionated aspect. From the analysis, it is concluded that JA’s text is inscribed in the ‘polemic discourse’ genre, asserting itself of the polemic-humoristic argumentative modality. For this purpose, the dissent and the ‘surprise effect’ present in his textual production contribute. In this context, the author contributes to the construction of democracy and citizenship in Mozambique, using the dichotomization, negative polarity, and other dialogical categories in the construction of a discourse of social intervention.